Psoriatic Arthritis 2018
DOI: 10.1136/annrheumdis-2018-eular.2692
|View full text |Cite
|
Sign up to set email alerts
|

AB0915 Bone mineral density and fracture frequencies in patients with psoriasis or psoriasis arthritis

Abstract: BackgroundReports on the prevalence of osteoporosis, osteoporotic fractures and risk factors for osteoporosis in patients with Psoriasis or Psoriasisarthritis are scarce, and the published results on this are, at least in part, contradictory. Additionally, there is no firm understanding of the impact of potential risk factors such as smoking and low Vitamin D (Vit D) levels have on the occurrence of osteoporotic fractures in this patient group.ObjectivesRh-GIOP is an ongoing prospective study monitoring glucoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Several Ps treatments have been shown to interfere with physiological bone metabolism, including corticosteroids, 35 MTX, 36 CsA 37 . In Ps there is a dichotomy; AZA has been associated with overall increased fracture risk 38 and glucocorticoids, 39 CsA, 38 and MTX 38,40 do not appear to impact bone health negatively. A large‐scale observational study, drawing on UK Biobank genomic data and using Mendelian randomization to evaluate the causal effect, concluded that the effect of PsA on OP was not genetically determined but secondary to treatment with medication (MTX, CsA) 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Several Ps treatments have been shown to interfere with physiological bone metabolism, including corticosteroids, 35 MTX, 36 CsA 37 . In Ps there is a dichotomy; AZA has been associated with overall increased fracture risk 38 and glucocorticoids, 39 CsA, 38 and MTX 38,40 do not appear to impact bone health negatively. A large‐scale observational study, drawing on UK Biobank genomic data and using Mendelian randomization to evaluate the causal effect, concluded that the effect of PsA on OP was not genetically determined but secondary to treatment with medication (MTX, CsA) 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Freier et al 27,28 . conducted two prospective cohort studies in Germany, investigating women aged around 60 with mild to severe psoriasis, over a period of 2 years.…”
Section: Prevalence Of Osteoporosis and Osteopenia In Patients With P...mentioning
confidence: 99%
“…18 In 2017, Lajevardi et al 25 reported 64 patients aged 44 AE 17 years with chronic psoriasis (duration 27 AE 5 years in a cross-sectional study in Iran, and found that BMD levels were lower in males, 25 similar to the results from the previous study by Dreiher et al 20 The prevalence of osteopenia (43.8%) and osteoporosis (12.5%) showed that BMD reduction was associated with psoriasis, 23,26 smoking and lack of physical activity. 25 Freier et al 27,28 conducted two prospective cohort studies in Germany, investigating women aged around 60 with mild to severe psoriasis, over a period of 2 years. The prevalence of osteopenia and osteoporosis in patients with psoriasis was similar to the normal population, which contrast with the existing evidence at the time, and the authors suggest that further investigation was needed.…”
Section: Prevalence Of Osteoporosis and Osteopenia In Patients With P...mentioning
confidence: 99%
See 2 more Smart Citations